Recent Developments in Graphene Oxide/Epoxy Carbon Fiber-Reinforced Composites - Keyte, John; Pancholi, Ketan; Njuguna, James (Frontiers in Materials, 2019)
The two-dimensional macro molecule graphene and its derivatives have widely been investigated for their application as nanofiller in carbon fibre-reinforced composites (CFRC). Research has progressed from techniques that simply mix graphene as a mixing constituent within the composite material to more complex examples where graphene is covalently bonded to fibre, matrix or both via multiple reaction steps. This field of research is multi-disciplinary whereby branches of materials, engineering, polymer science, physics and chemistry often overlap. From the materials engineering perspective, the desire is to discover the novel materials targeting industrial applications and obtain a full understanding of the graphene oxide chemistry and interaction of graphene oxide with a polymer matrix. To date, most of the research is targeted at (i) improving the fibre / matrix interface properties and / or (ii) improving the dispersion of nanofiller within the matrix; both of these factors ultimately improve composite performance. Organising that information critically can lead to emergence of a generalization of material design. Therefore, the objective of this work is to critically review current state of art in the field of graphene oxide / epoxy CFRCs and propose the design rules based on current scientific trend and common themes for future works.